International society and sustainable development goals - Durán y Lalaguna, Paloma (Colección de libros electrónicos de ULoyola, 2016)
The Chair on Development and Poverty Eradication aims at promoting the engagement of universities around the world in achieving the 2030 Agenda for Sustainable Development through training, advocacy and research. It was established by the United Nations? Sustainable Development Goals Fund (SDG-F). As part of the Chair?s work, this book introduces an overall view of the Sustainable Development Goals. Authors have conducted specific studies on each of the SDGs, as well as introduction and conclusions, which could be extremely useful to readers. The international community needs to make an authentic effort to achieve the SDGs. To accomplish this task, academic studies should play a key role. By researching and studying the SDGs, in all their different dimensions, academia can contribute to inform policy making for eradicating poverty and ensuring the welfare of everyone, leaving no one behind. These are the main finalities of this book. The analysis and recommendations of this report do not necessarily reflect the official views of the